Method for realizing selective green separation of nickel and cobalt through regulation and control of metal ion morphology
By introducing H+ and Cl- into the nickel-cobalt mixed solution to regulate the ionic morphology and using MOF-based composite adsorbent for selective adsorption and separation, the problems of low separation efficiency and secondary pollution in the prior art are solved, and high efficiency is achieved , separation of green nickel-cobalt.
Patent Information
- Application Number
- CN202311023700.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-14
- Publication Date
- 2025-02-21
AI Technical Summary
The existing nickel-cobalt solutions have low selective separation or adsorption separation efficiency. The desorption process uses chemical solvents, which produces large amounts of waste liquid, resulting in secondary pollution and other problems.
By introducing H+ and Cl- into the nickel-cobalt mixed solution, the metal ion form is regulated, and the MOF-based composite adsorbent is used for selective adsorption and separation. The adsorbed adsorbent is desorbed through water without chemical reagents.
It realizes efficient selective adsorption and separation of nickel and cobalt, avoids the use of chemical reagents, reduces the generation of waste liquid, and achieves the effect of green separation.
Smart Images

Figure CN119491109A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary metal resource utilization, and in particular to a method for realizing selective green separation of nickel and cobalt by regulating the morphology of metal ions. Background Art
[0002] Nickel and cobalt, as important strategic reserve metals in my country, play an important role in industrial production and new energy fields. Due to similar physical and chemical properties, they often coexist and co-exist in minerals or secondary resources. Therefore, separating and recovering nickel and cobalt from solutions is of great significance to the recycling of metal resources.
[0003] Common methods for separating nickel and cobalt are solvent extraction, adsorbent adsorption, and chemical precipitation. Among them, adsorbent adsorption is regarded as one of the important technologies for selective separation of nickel and cobalt because of its advantages such as easy operation, simple process, and high separation efficiency. However, at present, research on the selective separation of metals with similar chemical properties by adsorption mainly focuses on the development of new adsorbents and the modification of adsorbents, aiming to achieve the separation of similar metals through the design of adsorption materials. For example, Zhang et al. (Environmental Science: Nano, 2020) used lignin as the skeleton and glutaraldehyde as the cross-linking agent, and cross-linked hyperbranched polyethyleneimine with chitosan to obtain a porous polyethyleneimine functionalized chitosan / lignin composite sponge with a semi-interpenetrating three-dimensional network structure. By exerting the chelating effect of the amino functional groups in the composite material, the efficient removal of mercury ions in mercury-containing wastewater was achieved. In order to improve the adsorption and water stability of Zr-MOF adsorbent, Luo et al. (Chemosphere, 2022) combined Zr-MOF with polymers by a simple drop method to achieve efficient removal of lead ions in wastewater. Ji et al. (Water Research, 2021) achieved efficient desorption of copper ions after adsorption by creating carboxylic acid groups with different degrees of polymerization on the surface of MOF. Patent CN108620033A discloses an iron-modified chitosan / vermiculite composite material for simultaneously removing anions and cations in water, and its preparation method and application method, which achieves the simultaneous removal of chromium and cadmium in wastewater. Patent CN109608655A discloses a bifunctional group MOFs material and its preparation method and application, which achieves the simultaneous removal of anions and cations in water by simultaneously modifying acid functional groups and tertiary amine functional groups on the MOF base. A search of published research articles and open patents in the same field shows that the treatment of solutions containing metal ions by adsorption mainly considers the removal efficiency of ions, and there is less research on selective separation. Chen et al. (Rare Metals, 2010) obtained a composite adsorbent for selective extraction of cobalt by combining HPD-100 styrene-divinylbenzene macroporous adsorption resin and P507 extractant. The stripped cobalt solution was electrolyzed to obtain high-purity cobalt. The total impurity content was less than 10×10 -6 %. However, in this process, the adsorbent for adsorbing cobalt ions needs to be eluted by a hydrochloric acid solution, producing acidic wastewater.
[0004] In view of the low efficiency of selective separation or adsorption separation of existing nickel-cobalt solutions, the use of chemical solvents in the desorption process, the large amount of waste liquid generated, and the secondary pollution caused by the problems such as how to find a method to efficiently achieve selective adsorption separation of nickel and cobalt and achieve desorption without chemical reagents is a technical problem that needs to be solved urgently. Summary of the invention
[0005] The present invention provides a method for realizing selective green separation of nickel and cobalt by regulating the form of metal ions, and aims to realize selective adsorption separation of cobalt and nickel effectively and greenly.
[0006] The present invention relates to a method for realizing the selective green separation of nickel and cobalt by regulating the morphology of metal ions. The method comprises the following steps: (1) introducing H into a nickel-cobalt mixed solution; + and Cl - , to obtain a mixed liquid to be separated; (2) allowing the mixed liquid to be separated from step (1) to contact with a MOF-based composite adsorbent for adsorption separation, to obtain an adsorbed adsorbent and a separated solution; (3) allowing the adsorbed adsorbent from step (2) to contact with water for desorption, to obtain a regenerated adsorbent and a desorbed solution.
[0007] Optionally, in step (1): Cl introduced into the nickel-cobalt mixed solution - and H + The molar ratio of Cl is (0.5-5):1; Cl introduced into the nickel-cobalt mixed solution - The ratio of the molar number of to the total molar number of nickel and cobalt in the nickel-cobalt mixed solution is (120-6000):1.
[0008] Optionally, in step (1): in the nickel-cobalt mixed solution, the concentrations of nickel and cobalt are each independently 1.0 mmol / L -1 -50mmol L -1 Based on the volume of the mixed solution to be separated, the H + and Cl - The concentrations were independently 7-9 mol / L -1 .
[0009] Optionally, in step (1), a hydrochloric acid solution is added to the nickel-cobalt mixed solution to introduce H + and Cl - ;
[0010] The mass concentration of the hydrochloric acid solution is 30% to 50%.
[0011] Optionally, in step (2), the MOF-based composite adsorbent comprises a MOF substrate and a quaternary ammonium group adsorbed on the MOF substrate;
[0012] The MOF substrate is selected from a MOF substrate with a carboxylic acid functional group, preferably UiO-66 or UiO-67;
[0013] The quaternary ammonium group is selected from (R3R2R1)N + , wherein R1, R2 and R3 are each independently selected from a C1-C16 alkyl group;
[0014] The MOF-based composite adsorbent is prepared from the MOF substrate and a quaternary ammonium salt containing the quaternary ammonium group; the loading amount of the quaternary ammonium group on the MOF substrate is 1% to 20%, based on the mass of the quaternary ammonium group and the MOF substrate.
[0015] Optionally, in step (2), the adsorption separation adopts static adsorption or dynamic adsorption.
[0016] Optionally, the static adsorption comprises: adding the MOF-based composite adsorbent to the mixed solution to be separated obtained from step (1), and then performing constant temperature oscillation to separate the adsorbed adsorbent and the separated solution;
[0017] The addition amount of the MOF-based composite adsorbent is 0.1 g L -1 -40g L -1 , based on the volume of the nickel-cobalt mixed solution; and / or,
[0018] The constant temperature oscillation time is greater than or equal to 2 hours, and the rotation speed is 10 r min -1 -1000r min -1 .
[0019] Optionally, the desorption method in step (3) comprises: contacting the adsorbent after the adsorption in step (2) with water for 1-2 hours; the volume of the water is greater than or equal to 2 mL g -1 , based on the mass of the MOF-based composite adsorbent in step (2); preferably, the volume of water is 5 to 20 mL g -1 , based on the mass of the MOF-based composite adsorbent described in step (2).
[0020] Optionally, the dynamic adsorption comprises: loading the MOF-based composite adsorbent on an adsorption column, and then allowing the mixed solution to be separated from step (1) to flow through the adsorption column to obtain an adsorption column after adsorption and the separated solution, wherein the adsorption column is loaded with the adsorbent after adsorption;
[0021] The flow rate of the mixed liquid to be separated is 1 BV h -1 -50BVh -1 .
[0022] Optionally, the desorption method in step (3) comprises: allowing water to flow through the adsorption column after adsorption, with a flow rate of water of 1 BV h -1 -50BVh -1 .
[0023] Beneficial effects:
[0024] The present invention introduces H + and Cl- The ion form in the nickel-cobalt mixed solution is regulated, and then the cobalt ions in the nickel-cobalt mixed solution are effectively and selectively adsorbed by the MOF-based composite adsorbent. The adsorbed adsorbent can be well desorbed by water, realizing green desorption without the use of chemical reagents, and achieving green and efficient separation of nickel and cobalt. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is an electron microscope photograph of the MOF-based adsorbent prepared in Example 1;
[0026] Figure 2 This is an electron microscope photograph of the MOF-based adsorbent prepared in Example 2. DETAILED DESCRIPTION
[0027] The present application is further described in detail below through the accompanying drawings and embodiments. Through these descriptions, the characteristics and advantages of the present application will become clearer and more specific.
[0028] The word "exemplary" is used exclusively herein to mean "serving as an example, embodiment, or illustration." Any embodiment described herein as "exemplary" is not necessarily to be construed as preferred or advantageous over other embodiments. Although various aspects of the embodiments are shown in the drawings, the drawings are not necessarily drawn to scale unless otherwise noted.
[0029] In addition, the technical features involved in different embodiments of the present application described below can be combined with each other as long as they do not conflict with each other.
[0030] The present invention relates to a method for realizing selective green separation of nickel and cobalt by regulating the morphology of metal ions, the method comprising the following steps:
[0031] (1) Introducing H into the nickel-cobalt mixed solution + and Cl - , and obtain the mixed liquid to be separated;
[0032] (2) contacting the mixed solution to be separated from step (1) with a MOF-based composite adsorbent for adsorption separation to obtain an adsorbed adsorbent and a separated solution;
[0033] (3) contacting the adsorbent after the adsorption in step (2) with water for desorption, thereby obtaining a regenerated adsorbent and a desorption solution.
[0034] It should be noted that in step (1), the nickel-cobalt mixed solution refers to a solution containing both nickel ions and cobalt ions; + represents hydrogen ion, Cl -The nickel-cobalt mixed solution for selective green separation of nickel and cobalt in the present invention may be a mixed solution that has been treated with impurities in the early stage, and does not contain silver ions that can consume Cl - ions or substances, nor does it contain hydroxide or other substances that can consume H + ions or substances.
[0035] The present invention simultaneously introduces H + and Cl - The main occurrence forms of nickel and cobalt ions in the solution are regulated, or in other words, the adsorption difference between the main existence forms of cobalt ions and the main existence forms of nickel ions and the MOF-based composite adsorbent is maximized by regulating the occurrence forms of the dominant ions in the solution, so as to achieve effective selective separation of nickel and cobalt, and to achieve selective adsorption separation of nickel and cobalt and green regeneration of the adsorbent without chemical reagents by using anionic adsorbents. The separated solution obtained from step (2) is a solution rich in nickel ions, and the desorption solution obtained from step (3) is a solution rich in cobalt ions.
[0036] It should be noted that in the method of the present invention, in step (1), H is introduced into the nickel-cobalt mixed solution. + and Cl - When [CoCl3] - , [CoCl4] 2- When these two forms account for the largest proportion of the total cobalt, nickel is mainly in the form of [Ni(H2O)6] 2+ , NiCl2(H2O) and [NiCl(H2O)] + At this time, the main forms of nickel and cobalt have the greatest difference in adsorption performance on the MOF-based composite adsorbent, which can most effectively achieve selective adsorption separation. At this time, stop introducing H + and Cl - hour.
[0037] According to a specific embodiment of the method of the present invention, in step (1):
[0038] The Cl introduced into the nickel-cobalt mixed solution - and H + The molar ratio is (0.5-5):1;
[0039] The Cl introduced into the nickel-cobalt mixed solution - The ratio of the molar number of to the total molar number of nickel and cobalt in the nickel-cobalt mixed solution is (120-6000):1.
[0040] It should be noted that in step (1), by controlling the Cl introduced into the nickel-cobalt mixed solution as above, -and H + The molar ratio of Cl - The ratio of the molar number of nickel ions to the total molar number of cobalt ions in the nickel-cobalt mixed solution can well realize the regulation of the ionic forms of nickel and cobalt in the nickel-cobalt mixed solution, so that nickel and cobalt are adjusted to their respective dominant forms, and the dominant forms of ions of the two can be effectively selectively adsorbed and separated by the MOF-based composite adsorbent, so that cobalt ions are adsorbed on the MOF-based composite adsorbent, while nickel ions are retained in the solution after separation. The MOF-based composite adsorbent adsorbed with cobalt ions can be desorbed by washing or soaking with water to regenerate the adsorbent.
[0041] It should be noted that, specifically, in step (1), the Cl introduced into the nickel-cobalt mixed solution - and H + The molar ratio of Cl introduced into the nickel-cobalt mixed solution can be 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, etc. - The ratio of the molar number of nickel to the total molar number of nickel and cobalt in the nickel-cobalt mixed solution can be 200:1, 300:1, 350:1, 400:1, 450:1, 500:1, 600:1, 700:1, 750:1, 800:1, 900:1, 1000:1, 2000:1, 3000:1, 4000:1 and 5000:1, etc.
[0042] According to a specific embodiment of the method of the present invention, in step (1): in the nickel-cobalt mixed solution, the concentrations of nickel and cobalt are independently 1.0 mmol L -1 -50mmol L -1 ;
[0043] Based on the volume of the mixed solution to be separated, the amount of H introduced + and Cl - The concentration of each is independently greater than or equal to 6 molL -1 .
[0044] It should be noted that, preferably, in the nickel-cobalt mixed solution, the concentrations of nickel and cobalt are each independently 25 mmol L -1 In the nickel-cobalt mixed solution, in addition to nickel ions and cobalt ions, the anions contained may include but are not limited to nitrate, sulfate and chloride ions (the amount of chloride ions initially contained is much smaller than the amount of chloride ions added in step (1) and can be ignored).
[0045] In the mixed solution to be separated, the H + and Cl - The concentration of each is independently greater than or equal to 6 mol L -1For example, a solution containing H + and Cl - One or more substances, according to the added substances in the solution to contain H + and Cl - All released, the introduced H + and Cl - The molar number of each of the two is 6.5 mol, and the volume of the mixed solution to be separated after the feeding is completed is 1 L. Then, in the mixed solution to be separated obtained in step (1), the amount of H introduced is + and Cl - The concentrations were 6.5 mol L -1 .
[0046] As a preferred embodiment, in step (1): in the nickel-cobalt mixed solution, the concentrations of nickel and cobalt are independently 1.0 mmol L -1 -50mmol L -1 Based on the volume of the mixed solution to be separated, the H + and Cl - The concentration of each was independently 7-9 mol L -1 .
[0047] It should be noted that when the concentrations of nickel and cobalt are each independently 1.0 mmol L -1 -50mmol L -1 When H + and Cl - The concentration of each was independently 7-9 mol L -1 When the nickel and cobalt are adsorbed on the MOF-based composite adsorbent, the nickel and cobalt can be better regulated to form ions with a larger difference in adsorption performance on the MOF-based composite adsorbent, so as to more effectively achieve green separation by selective adsorption.
[0048] According to a specific embodiment of the method of the present invention, in step (1), a hydrochloric acid solution is added to the nickel-cobalt mixed solution to introduce H + and Cl - .
[0049] It should be noted that by adding Cl - The ionic forms of cobalt and nickel in the solution can be regulated by adding H + To enable cobalt and nickel to maintain the preferred or target form more stably, H + and Cl -The inventors of the present application analyzed the nickel-cobalt solution by MCR-ALS combined with UV-visible spectroscopy. The study showed that in step (1), the main occurrence form of ions in the nickel-cobalt mixed solution was regulated by adding hydrochloric acid solution. When the hydrochloric acid concentration in the solution system reached (or was greater than) 6 mold m -3 When the concentration is 7-9 mol L -1 When the cobalt ions in the solution are mainly [CoCl4] 2- and [CoCl3] - Nickel ions exist mainly in the form of [Ni(H2O)6] 2+ , NiCl2(H2O) and [NiCl(H2O)] + The nickel and cobalt exist in different ionic forms, and the adsorption difference or selective adsorption capacity difference of the MOF-based composite adsorbent is the largest.
[0050] In step (2), the mixed solution to be separated is contacted with a MOF-based composite adsorbent, the quaternary ammonium group in the MOF-based composite adsorbent is loaded on the MOF substrate, and the chloride ions in the solution are rapidly adsorbed onto the quaternary ammonium group of the composite adsorbent. The molecular dynamics simulation analysis shows that the hydrochloric acid concentration is greater than 6 mol dm -3 The process of the nickel-cobalt dominant ion occurrence form combining with the quaternary ammonium group shows that the chlorinated dominant ion occurrence form of cobalt combines with the quaternary ammonium group within 0.2ns [CoCl4] 2- , [CoCl3] - Compete with the chloride ions bound to the quaternary ammonium groups, and bind to the positively charged quaternary ammonium groups to be loaded on the MOF-based composite adsorbent, while [Ni(H2O)6] 2+ , NiCl2(H2O) and [NiCl(H2O)] + Since the binding energy with the quaternary ammonium group is weak, it remains in the solution.
[0051] In general, by regulating the dominant form of nickel-cobalt chloride ions in the solution, the differentiated binding of nickel-cobalt chloride ions with the adsorbent can be achieved, thereby realizing highly selective and green separation of nickel and cobalt.
[0052] In step (3), the MOF-based composite adsorbent adsorbing cobalt ions is separated from the solution and then contacted with pure water. Under the competitive effect of water molecules, the [CoCl3] - and [CoCl4] 2- Converted to Co 2+ , [CoCl] +The quaternary ammonium groups carried by the MOF-based composite adsorbent are cations. Therefore, the cobalt ions converted into positive charges cannot continue to adsorb on the quaternary ammonium groups, and are desorbed from the adsorbent and remain in the desorption liquid. The separated solution after separation from the adsorbent is a solution rich in nickel ions, and the desorption liquid washed from the adsorbent by water is a solution rich in cobalt ions. The green separation of nickel and cobalt ions is thus completed.
[0053] According to a specific implementation of the method of the present invention, the mass concentration of the hydrochloric acid solution can be 30% to 50%.
[0054] It should be noted that in step (1), by adding hydrochloric acid solution to the nickel-cobalt mixed solution to introduce H + and Cl - When adding the hydrochloric acid solution of the above concentration, it is beneficial to achieve a better separation effect.
[0055] It should be noted that in the method of realizing the selective green separation of nickel and cobalt by regulating the metal ion morphology of the present application, the introduction of H + and Cl - As a variation of the embodiment, in step (1), a soluble chloride ion salt and a H-containing salt may be added to the nickel-cobalt mixed solution. + Acid; Specifically, the soluble chloride ion salt that can be added includes but is not limited to a combination of one or more of sodium chloride, potassium chloride, magnesium chloride, calcium chloride, etc., and the H-containing + The acid includes, but is not limited to, one or more combinations of nitric acid, sulfuric acid, hydrofluoric acid, formic acid, acetic acid, phosphoric acid, citric acid, and the like.
[0056] According to a specific embodiment of the method of the present invention, in step (2), the MOF-based composite adsorbent comprises a MOF substrate and a quaternary ammonium group adsorbed on the MOF substrate;
[0057] The MOF substrate is selected from a MOF substrate with a carboxylic acid functional group, preferably UiO-66 or UiO-67;
[0058] The quaternary ammonium group is selected from (R3R2R1)N + , wherein R1, R2 and R3 are each independently selected from a C1-C16 alkyl group;
[0059] The MOF-based composite adsorbent is prepared from the MOF substrate and a quaternary ammonium salt containing the quaternary ammonium group; the loading amount of the quaternary ammonium group on the MOF substrate is 1% to 20%, based on the mass of the quaternary ammonium group and the MOF substrate.
[0060] It should be noted that in the MOF-based composite adsorbent, an acid-resistant MOF with a stable pore structure is selected as a carrier of the quaternary ammonium group molecule, the MOF substrate can be selected from zeolite imidazoles, and the metal center of the MOF substrate is preferably zirconium. + In the above, R1, R2 and R3 can be independently selected from ethyl, propyl, butyl, alkyl having 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, and 15 carbon atoms.
[0061] The guest molecules with active functional groups can be fixed into the MOF pores by vacuum-assisted methods. Specifically, the preparation process of MOF-based composite adsorbents can include the following steps:
[0062] (1) Take a MOF substrate and a guest molecule (quaternary ammonium salt) solution with a mass ratio between 1:1-1:10 (the ratio of MOF substrate to quaternary ammonium salt) and mix them thoroughly. (2) Maintain the temperature range of 90-150℃ in a vacuum drying oven and continue stirring for 24-72h. (3) The obtained product is separated by a centrifuge and the unfixed guest molecules are washed with a large amount of clean water. Then, the material is washed several times with anhydrous acetone to remove moisture from the MOF pores. (4) Finally, the sample is vacuum dried at 50-70℃ overnight. The porous MOF loaded with quaternary ammonium groups is used as the adsorbent in this process. The quaternary ammonium groups are fixed to the pores of the MOF by vacuum assistance, thereby realizing the design of the adsorbent.
[0063] It should be noted that when the MOF-based composite adsorbent is prepared based on a MOF substrate such as UiO-66 or UiO-67 with a mass ratio of 1:1 and hexadecyltrimethylammonium bromide or tetradecyltrimethylammonium bromide, the prepared MOF-based composite adsorbent is tested by XPS, and the loading amount based on the mass of the quaternary ammonium group and the MOF substrate is 1-20%.
[0064] According to a specific embodiment of the method of the present invention, in step (2), the adsorption separation adopts static adsorption or dynamic adsorption.
[0065] It should be noted that in the method of the present application for achieving selective green separation of nickel and cobalt by regulating the metal ion morphology, adsorption separation can be performed by static adsorption or dynamic adsorption, but is not limited to these two specific adsorption methods. Any adsorption separation method that can bring the mixed liquid to be separated from step (1) into contact with the MOF-based composite adsorbent is applicable, and the present invention is not limited thereto.
[0066] According to a specific embodiment of the method of the present invention, the static adsorption comprises:
[0067] Adding the MOF-based composite adsorbent to the mixed solution to be separated obtained in step (1), and then oscillating at a constant temperature to separate the adsorbent after adsorption and the separated solution;
[0068] The addition amount of the MOF-based composite adsorbent is 0.1 g L -1 -40g L -1 , based on the volume of the nickel-cobalt mixed solution; and / or,
[0069] The constant temperature oscillation time is greater than or equal to 2 hours, and the rotation speed is 10 r min -1 -1000r min -1 .
[0070] It should be noted that when static adsorption is used, the constant temperature oscillation time can be longer, such as more than 12 h, and the addition amount of the MOF-based composite adsorbent can be specifically 2 g L -1 , 5g L -1 , 8g L -1 , 10g L -1 , 15g L -1 , 20g L -1 , 25g L -1 , 30gL -1 , 35g L -1 etc., based on the volume of the nickel-cobalt mixed solution. Performing the static adsorption under the above conditions can achieve better separation effect.
[0071] According to a specific embodiment of the method of the present invention, the desorption method in step (3) comprises:
[0072] Allow the adsorbent after the adsorption in step (2) to contact with water for 1-2 hours;
[0073] The volume of water is greater than or equal to 2 mL g -1 , based on the mass of the MOF-based composite adsorbent in step (2);
[0074] Preferably, the volume of water is 5 to 20 mL g -1 , based on the mass of the MOF-based composite adsorbent described in step (2).
[0075] It should be noted that in the method of the present invention, the adsorbent does not need to be desorbed by chemical reagents. The Co ions adsorbed on the MOF-based composite adsorbent can be desorbed only by contact with water, thereby completing the regeneration of the adsorbent.
[0076] According to a specific embodiment of the method of the present invention, the dynamic adsorption comprises:
[0077] The MOF-based composite adsorbent is loaded on an adsorption column, and then the mixed solution to be separated from step (1) is passed through the adsorption column to obtain an adsorption column after adsorption and the separated solution. At this time, the adsorption column is loaded with the adsorbent after adsorption;
[0078] The flow rate of the mixed liquid to be separated is 1 BV h -1 -50BVh -1 .
[0079] It should be noted that when dynamic adsorption is used, at a flow rate of 1 BV h -1 or 1.5BV h -1 When running at 10BV, the selective adsorption and separation of nickel ions and cobalt ions can be well completed.
[0080] According to a specific embodiment of the method of the present invention, the desorption method in step (3) comprises:
[0081] Water is allowed to flow through the adsorption column after adsorption at a flow rate of 1 BV h -1 -50BVh -1 .
[0082] It should be noted that in dynamic adsorption, the desorption of adsorbed ions can be achieved by allowing water to flow through the adsorption column at the same flow rate as during adsorption. Specifically, during desorption, water can be allowed to flow through the adsorption column at a flow rate of 1 BV h -1 or 1.5BV h -1 Running 5BV can achieve good desorption without the use of chemical reagents, without generating a large amount of waste liquid, and effectively avoiding secondary pollution.
[0083] In summary, the present application can use the addition of hydrochloric acid during the adsorption process to adjust the Co 2+ , [CoCl] + 、CoCl2、[CoCl3] - , [CoCl4] 2- 、[Ni(H2O)6] 2+ 、[NiCl(H2O)] + , the occurrence form of NiCl2 ions, by adjusting the dominant form of cobalt in the adsorption process to [CoCl3] - , [CoCl4] 2- The dominant forms of nickel are regulated as NiCl2(H2O), [Ni(H2O)6] 2+ 、[NiCl(H2O)] + , achieving the combination of cobalt ions and MOF-based adsorbents loaded with quaternary ammonium groups. The dominant form of cobalt in the desorption process is regulated to Co 2+ , [CoCl] +, CoCl2, thereby achieving the desorption of cobalt ions after adsorption. The entire separation process achieves the regulation of the dominant occurrence form of nickel and cobalt by adjusting the properties of the solution, thereby changing its binding ability with the quaternary ammonium functional group. Without the need for an acidic eluent, the chemical-free desorption of cobalt ions after adsorption is achieved by immersion or elution in deionized water, ultimately achieving the effect of efficient and green separation of nickel and cobalt. The use of chemical-free desorption agents avoids the problems of secondary pollution and high desorption agent costs during the desorption process of adsorption materials.
[0084] The present invention is further described in detail by way of examples below, but the present invention is not limited thereto. In the following examples, unless otherwise specified, the experimental instruments and raw materials involved are all commercially available products.
[0085] The UiO-66 and UiO-67 used in the following examples were purchased from Xianfeng Nanomaterial Technology Co., Ltd.
[0086] It should be noted that in the following examples, after the addition of hydrochloric acid solution, the solution volume did not change much, and the H introduced by adding hydrochloric acid was calculated. + or Cl - The number of moles can be calculated from the initial solution volume.
[0087] Example 1
[0088] Nickel sulfate and cobalt sulfate were used to prepare 100 mL of the initial solution, where the concentrations of nickel and cobalt were 500 mg L -1 . Add hydrochloric acid solution (36 mass %) dropwise to ensure that the concentration of hydrochloric acid in the solution reaches 8 mol L -1 .
[0089] Weigh 2.0 g of anionic adsorbent and add it to the above solution, then place it in a constant temperature oscillator at 25 °C and rotate at 200 r min -1 Then, the adsorbent after adsorption was separated, and 20 mL of pure water was used to fully contact the adsorbent for 1 hour to obtain a regenerated adsorbent and a desorption solution containing mainly cobalt ions.
[0090] The preparation method of the adsorbent is as follows: according to the mass ratio of UiO-67 and hexadecyltrimethylammonium bromide of 1:1, UiO-67 and hexadecyltrimethylammonium bromide solution (concentration of 10 mol / L) are fully mixed, maintained at 120°C in a vacuum drying oven, and stirred continuously for 48 hours. The obtained product is separated by a centrifuge and the unfixed hexadecyltrimethylammonium bromide is washed with a large amount of clean water, and then the material is washed several times with anhydrous acetone to remove moisture in the MOF pores. Finally, the sample is vacuum dried at 60°C overnight to obtain Figure 1 Target anion adsorbents shown.
[0091] Three sets of parallel experiments, the results are shown in Table 1:
[0092] Table 1
[0093]
[0094] Example 2
[0095] Nickel sulfate and cobalt sulfate were used to prepare 100 mL of the initial solution, where the concentrations of nickel and cobalt were 300 mg L -1 Hydrochloric acid solution (36 mass %) was added dropwise to ensure that the concentration of hydrochloric acid in the solution reached 7.5 mol L -1 .
[0096] Weigh 1.5 g of anionic adsorbent and add it to the above solution, then place it in a constant temperature oscillator at 25 °C and rotate at 200 r min -1 Then, the adsorbent after adsorption was separated, and 20 mL of pure water was used to fully contact the adsorbent for 1 hour to obtain a regenerated adsorbent and a desorption solution containing mainly cobalt ions.
[0097] The preparation method of the adsorbent is as follows: according to the mass ratio of UiO-67 and hexadecyltrimethylammonium bromide of 1:1, UiO-67 and hexadecyltrimethylammonium bromide solution (concentration of 10 mol / L) are fully mixed, maintained at 120°C in a vacuum drying oven, and stirred continuously for 48 hours. The obtained product is separated by a centrifuge and the unfixed hexadecyltrimethylammonium bromide is washed with a large amount of clean water, and then the material is washed several times with anhydrous acetone to remove moisture in the MOF pores. Finally, the sample is vacuum dried at 60°C overnight to obtain Figure 2 Target anion adsorbents shown.
[0098] Three sets of parallel experiments, the results are shown in Table 2:
[0099] Table 2
[0100]
[0101] Example 3
[0102] 500 mL of initial solution was prepared using nickel sulfate and cobalt sulfate, where the concentrations of nickel and cobalt were 700 mg L -1 Hydrochloric acid solution (36 mass %) was added dropwise to ensure that the concentration of hydrochloric acid in the solution reached 9 mol L -1 .
[0103] Weigh 5 g of anionic adsorbent and add it to the above solution, then place it in a constant temperature oscillator at 25 °C and rotate at 200 r min -1Then, the adsorbent after adsorption was separated, and 50 mL of pure water was used to fully contact the adsorbent for 2 hours to obtain a regenerated adsorbent and a desorption solution containing mainly cobalt ions.
[0104] The preparation method of the adsorbent is as follows: according to the mass ratio of UiO-66 and tetradecyl trimethyl ammonium bromide 1:1, UiO-66 and tetradecyl trimethyl ammonium bromide solution (concentration of 10 mol / L) are fully mixed, maintained at 110°C in a vacuum drying oven, and stirred for 60 hours. The obtained product is separated by a centrifuge, and the unfixed tetradecyl trimethyl ammonium bromide is washed with a large amount of clean water, and then the material is washed several times with anhydrous acetone to remove moisture in the MOF pores. Finally, the sample is vacuum dried at 80°C overnight to obtain the target anion adsorbent.
[0105] Three sets of parallel experiments, the results are shown in Table 3:
[0106] Table 3
[0107]
[0108] Example 4
[0109] Use nickel sulfate and cobalt sulfate to prepare 200 mL of the initial solution, where the concentrations of nickel and cobalt are 600 mg L -1 Hydrochloric acid solution (36 mass %) was added dropwise to ensure that the concentration of hydrochloric acid in the solution reached 9 mol L -1 .
[0110] Weigh 5 g of anionic adsorbent and load it into a glass adsorption column with a water bath jacket (the inner diameter of the adsorption column is 10 mm and the height is 200 mm). Pass the above solution into the above adsorption column. The adsorption temperature is 25 °C and the adsorption flow rate is 1 BV h -1 Then, pure water was introduced into the adsorption column to desorb adsorbed ions and regenerate the adsorbent. The desorption flow rate was 1 BV h -1 , run 5BV, and obtain the regenerated adsorbent and the desorption solution containing ions mainly consisting of cobalt ions. The adsorbent used is the adsorbent of Example 3. Three sets of parallel experiments, the results are shown in Table 4:
[0111] Table 4
[0112]
[0113] Example 5
[0114] The initial solution of 100 mL was prepared using nickel sulfate and cobalt sulfate, where the concentrations of nickel and cobalt were 800 mg L -1. Hydrochloric acid solution (36 mass %) was added dropwise to ensure that the concentration of hydrochloric acid in the solution reached 8 mol L -1 .
[0115] Weigh 7g of anionic adsorbent and load it into a glass adsorption column with a water bath jacket (the inner diameter of the adsorption column is 10mm and the height is 200mm). Pass the above solution into the above adsorption column. The adsorption temperature is 25℃ and the adsorption flow rate is 1.5BV h -1 Then, pure water was introduced into the adsorption column to desorb adsorbed ions and regenerate the adsorbent. The desorption flow rate was 1.5 BV h -1 , run 5BV, and obtain the regenerated adsorbent and the desorption solution containing ions mainly consisting of cobalt ions. The adsorbent used is the adsorbent of Example 1. Three sets of parallel experiments, the results are shown in Table 5:
[0116] Table 5
[0117]
[0118] Example 6
[0119] 500 mL of initial solution was prepared using nickel sulfate and cobalt sulfate, where the concentrations of nickel and cobalt were 700 mg L -1 Hydrochloric acid solution (36 mass %) was added dropwise to ensure that the concentration of hydrochloric acid in the solution reached 9 mol L -1 .
[0120] Weigh 5 g of anionic adsorbent and add it to the above solution, then place it in a constant temperature oscillator at 25 °C and rotate at 200 r min -1 The speed was oscillated for 4 hours. Then, the adsorbent after adsorption was separated, and 50 mL of pure water was used to fully contact the adsorbent for 2 hours to obtain the regenerated adsorbent and the desorption solution containing mainly cobalt ions. The above adsorbent was reused 5 times.
[0121] The preparation method of the adsorbent is as follows: according to the mass ratio of UiO-66 and tetradecyl trimethyl ammonium bromide of 1:1, UiO-66 and tetradecyl trimethyl ammonium bromide solution (concentration of 10 mol / L) are fully mixed, maintained at 110°C in a vacuum drying oven, and stirred continuously for 60 hours. The obtained product is separated by a centrifuge, and the unfixed tetradecyl trimethyl ammonium bromide is washed with a large amount of clean water, and then the material is washed several times with anhydrous acetone to remove moisture in the MOF pores. Finally, the sample is vacuum dried at 80°C overnight to obtain the target anion adsorbent.
[0122] The results of 5 cyclic adsorption experiments are shown in Table 6:
[0123] Table 6:
[0124]
[0125] Comparative Example 1
[0126] Nickel sulfate and cobalt sulfate were used to prepare 100 mL of the initial solution, where the concentrations of nickel and cobalt were 500 mg L -1 .
[0127] Weigh 2.0 g of anionic adsorbent and add it to the above solution, then place it in a constant temperature oscillator at 25 °C and rotate at 200 r min -1 The speed was oscillated for 2 hours. Then, the adsorbent after adsorption was separated, and 20 mL of pure water was used to fully contact the adsorbent for 1 hour to obtain the regenerated adsorbent and desorption solution. The adsorbent used was the adsorbent of Example 1. Three sets of parallel experiments, the results are shown in Table 7:
[0128] Table 7
[0129]
[0130] Comparative Example 2
[0131] The initial solution of 100 mL was prepared using nickel sulfate and cobalt sulfate, where the concentrations of nickel and cobalt were 700 mg L -1 .
[0132] Weigh 4.0 g of anionic adsorbent and add it to the above solution, then place it in a constant temperature oscillator at 25 °C, and add sodium chloride to make the chloride ion content in the solution reach 7 mol L -1 Then at 200rmin -1 The speed was oscillated for 2 hours. Then, the adsorbent after adsorption was separated, and 30 mL of pure water was used to fully contact the adsorbent for 2 hours to obtain the regenerated adsorbent and desorption solution. The adsorbent used was the adsorbent of Example 2. Three sets of parallel experiments, the results are shown in Table 8:
[0133] Table 8
[0134]
[0135] Comparative Example 3
[0136] 70 mL of initial solution was prepared using nickel sulfate and cobalt sulfate, where the concentrations of nickel and cobalt were 500 mg L -1 Weigh 4.0 g of anionic adsorbent and add it to the above solution, then place it in a constant temperature oscillator at 25°C and rotate at 300 rmin. -1The speed was oscillated for 2 hours. Then, the adsorbent after adsorption was separated, and 30 mL of pure water was used to fully contact the adsorbent for 2 hours to obtain the regenerated adsorbent and desorption solution. The adsorbent used was the adsorbent of Example 2. Three sets of parallel experiments, the results are shown in Table 9:
[0137] Table 9
[0138]
[0139] Comparative Example 4
[0140] The initial solution of 100 mL was prepared using nickel sulfate and cobalt sulfate, where the concentrations of nickel and cobalt were 800 mg L -1 7 g of anionic adsorbent was weighed and loaded into a glass adsorption column with a water bath jacket (the inner diameter of the adsorption column was 10 mm and the height was 200 mm). The adsorption temperature was 25 °C and the adsorption flow rate was 1.5 BV h -1 Then, pure water was introduced into the adsorption column to desorb adsorbed ions and regenerate the adsorbent. The desorption flow rate was 1.5 BV h -1 , run 5BV, and obtain the regenerated adsorbent and desorption solution. The adsorbent used is the adsorbent of Example 3. Three sets of parallel experiments, the results are shown in Table 10:
[0141] Table 10
[0142]
[0143] In the description of the present application, it should be noted that the terms "upper", "lower", "inside", "outside", "front", "back", "left", "right", etc. indicate directions or positional relationships based on the directions or positional relationships in the working state of the present application. They are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction. Therefore, they should not be understood as limitations on the present application.
[0144] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "install", "connect" and "connect" should be understood in a broad sense. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0145] The present application has been described above in conjunction with preferred embodiments, but these embodiments are only exemplary and serve only as an illustration. On this basis, various replacements and improvements may be made to the present application, all of which fall within the scope of protection of the present application.
Claims
1. A method for selective green separation of nickel and cobalt by regulating the morphology of metal ions, characterized in that: The method comprises the following steps: (1) Introducing H into the nickel-cobalt mixed solution + and Cl - , and obtain the mixed liquid to be separated; (2) contacting the mixed solution to be separated from step (1) with a MOF-based composite adsorbent for adsorption separation to obtain an adsorbed adsorbent and a separated solution; (3) contacting the adsorbent after the adsorption in step (2) with water for desorption, thereby obtaining a regenerated adsorbent and a desorption solution.
2. The method according to claim 1, characterized in that: In step (1): The Cl introduced into the nickel-cobalt mixed solution - and H + The molar ratio is (0.5-5):1; The Cl introduced into the nickel-cobalt mixed solution - The ratio of the molar number of to the total molar number of nickel and cobalt in the nickel-cobalt mixed solution is (120-6000):
1.
3. The method according to claim 2, characterized in that In step (1): In the nickel-cobalt mixed solution, the concentrations of nickel and cobalt are independently 1.0 mmol L -1 -50mmol L -1 ; Based on the volume of the mixed solution to be separated, the amount of H introduced + and Cl - The concentration of each was independently 7-9 mol L -1 .
4. The method according to any one of claims 1 to 3, characterized in that: In step (1), hydrochloric acid solution is added to the nickel-cobalt mixed solution to introduce H + and Cl - ; The mass concentration of the hydrochloric acid solution is 30% to 50%.
5. The method according to claim 1, characterized in that In step (2), the MOF-based composite adsorbent comprises a MOF substrate and a quaternary ammonium group adsorbed on the MOF substrate; The MOF substrate is selected from a MOF substrate with a carboxylic acid functional group, preferably UiO-66 or UiO-67; The quaternary ammonium group is selected from (R3R2R1)N + , wherein R1, R2 and R3 are each independently selected from a C1-C16 alkyl group; The MOF-based composite adsorbent is prepared from the MOF substrate and a quaternary ammonium salt containing the quaternary ammonium group; the loading amount of the quaternary ammonium group on the MOF substrate is 1% to 20%, based on the mass of the quaternary ammonium group and the MOF substrate.
6. The method according to claim 1, characterized in that In step (2), the adsorption separation adopts static adsorption or dynamic adsorption.
7. The method according to claim 6, characterized in that The static adsorption comprises: Adding the MOF-based composite adsorbent to the mixed solution to be separated obtained in step (1), and then oscillating at a constant temperature to separate the adsorbent after adsorption and the separated solution; The addition amount of the MOF-based composite adsorbent is 0.1 g L -1 -40g L -1 , based on the volume of the nickel-cobalt mixed solution; and / or, The constant temperature oscillation time is greater than or equal to 2 hours, and the rotation speed is 10 r min -1 -1000r min -1 .
8. The method according to claim 7, characterized in that The method for desorption in step (3) comprises: Allow the adsorbent after the adsorption in step (2) to contact with water for 1-2 hours; The volume of water is greater than or equal to 2 mL g -1 , based on the mass of the MOF-based composite adsorbent in step (2); Preferably, the volume of water is 5 to 20 mL g -1 , based on the mass of the MOF-based composite adsorbent described in step (2).
9. The method according to claim 6, characterized in that The dynamic adsorption comprises: The MOF-based composite adsorbent is loaded on an adsorption column, and then the mixed solution to be separated from step (1) is passed through the adsorption column to obtain an adsorption column after adsorption and the separated solution. At this time, the adsorption column is loaded with the adsorbent after adsorption; The flow rate of the mixed liquid to be separated is 1 BV h -1 -50BVh -1 .
10. The method according to claim 9, characterized in that The method for desorption in step (3) comprises: Water is allowed to flow through the adsorption column after adsorption at a flow rate of 1 BV h -1 -50BVh -1 .
Citation Information
Patent Citations
Iron modified chitosan / vermiculite composite material capable of removing anionic and cationic heavy metals at same time and preparation method and application thereof
CN108620033A
Bifunctional group MOFs material and preparation method and application thereof
CN109608655A